Visual Tract Integrity Before and After Gene Therapy in Congenital Achromatopsia - Abramovitch, Hillel; Bick, Atira S.; Guy, Nitzan; Elul, Deena; Mckyton, Ayelet; Banin, Eyal; Levin, Netta (Translational vision science & technology, 2025)
CNGA3 achromatopsia is a rare hereditary syndrome caused by dysfunction of cone photoreceptors. Visual information is therefore obtained only by rod photoreceptors, resulting in low acuity, photoaversion, and color blindness. Trials using gene therapy have been initiated recently, in which clinical improvement was subtle. To explain this suboptimal outcome, we used diffusion tensor imaging to assess visual pathway integrity in 3 CNGA3 achromatopsia patients before and after gene therapy, and compared them with 16 normally sighted adults. No significant differences from normal subjects in optic tract and radiation were detected. Fiber integrity reduction was observed in the occipitocallosal fibers. These differences showed some normalization after treatment, but intersubject variability was evident. Specifically, the observed changes were related to radial diffusivities, reflecting fiber myelination or glial cell alterations. Despite the fundamental role of cone photoreceptors in human sight, primary visual pathways in patients are comparable with those of healthy individuals and thereby fiber integrity is probably not an obstacle for recovery. Preliminary results suggest that the splenial fibers are less cohesive in naïve patients and regain some integrity after treatment. These findings add to previous reports on this rare population and suggest that novel information is processed within the visual cortex after treatment. Patients with complete color blindness were treated using a novel gene augmentation therapy. Unfortunately, the patients did not experience a sudden eureka moment of being able to perceive the full spectrum of colors. In this study, we rule out fiber disintegration as the cause of their limited recovery.